Economic survey of Latin America, 1962 - Organization of American States, General secretariat (Baltimore : John Hopkins Press, 1964)
This book is more than a compilation of facts and figures on the regions trade, balance of payments, and production, this 1962 survey seeks to analyze such data in the light of the Latin American countries' increasing efforts - as evidenced by the alliance for progress- to achieve higher rates of economic growth.
This survey was prepared in the Department of Economic Affairs of the Pan American Union.
rpm 30/05/2017
Loans
Keywords: Development planning; Tax; Agrarian Reforms; Production and Trade -- Central American; Primary Production export -- Central American; Latin America